A comparative study of visual impression between the types of two-dimensional design style in electronic game design (Al-Academy, 2024)
This research deals with a comparative study of the instant visual impressions between the types of two-dimensional designs in electronic game design. Instant impressions play a crucial role in attracting players, through the contrast of colors, shapes, lines, and degrees of shadow and light, which greatly affects the player's interaction. Four main principles were identified that the design must rely on to achieve a good visual impression: visual aesthetics, ease of use, emotional impact, and immersion and interaction. The results found that applying these principles to the design of two-dimensional games showed that cell shading type excel in generating positive visual and emotional impressions, especially among young age groups.The results highlight the importance of simplicity and color contrast in enhancing design aesthetics and player interaction It also showed that designs that resemble three-dimensional designs may be the most effective in generating positive responses, which enhances the player's experience and the continuity of interaction with the game.